Green supply chain management in developing countries : a study of factors and practices in Malaysia. - Rusli, Khairul Anuar; Abd Rahman, Azmawani; Ho, Jo Ann (2012)
With the increasing awareness on environmental sustainability issues, manufacturing firms nowadays start to think and act green. In addition, firms need to implement wise strategies in order to compromise with green issues without neglecting their business objectives. This paper reports the results of green practices and factors that lead firms to adopt green initiatives in Malaysia. Based on in depth interviews with four manufacturing companies, the results show that customers, marketing, regulations, competitive and internal factors are among the factors that encouraged firms to adopt green practices. This study also indicates manufacturers in Malaysia implement green purchasing, eco design and internal green practices in their operations. Therefore the findings will help to address the issues more appropriately and plan for better green supply chain management initiatives in the future aligning with effort and commitment shown by the government.